Knowledge, attitude and practices regarding tuberculosis among patients with TB attending tribal health care centres of H.D. Kote taluq, Mysuru district - Boralingiah, Prakash; Chauhan, Dennis (International Journal Of Community Medicine And Public Health, 2017)
Background: Tuberculosis is a major global health problem. The current global picture of tuberculosis shows continued progress but not fast enough. During the year 2013, an estimated 9 million people developed tuberculosis, which is equivalent to 126 cases per 100000 populations. High mortality rate due to TB among tribal clearly suggest the lack of awareness regarding the disease. The objective of the study was to assess the knowledge, attitude and practices of tribal patients regarding tuberculosis. Methods: A community based retrospective and prospective follow up study was undertaken during February 2014 to October 2014. All the patients attending VMH, Sargur and H.D. Kote Govt hospital who are diagnosed for TB in past three months and those who will be diagnosed for the same in the next 6 months were included for the study. A pretested structured questionnaire was used for data collection. Data collected was entered in Microsoft excel sheet and analyzed by using SPSS-22.0. Results: 6.3% of study subjects knew TB was caused by bacteria or some germs. Majority responded that TB was caused due to smoking, alcohol consumption, not taking food or sins of the past. 88% knew the symptoms of TB. 16% of the study subjects knew the organs affected by TB. More than half (66%) had unsatisfactory knowledge on TB on using a Knowledge score. 78.1% agreed that completely cured TB patients could marry. Conclusions: The present study highlights the lack of awareness among the tribal patients even though they receive the treatment from DOTS provider. Social stigma regarding TB is a barrier in successful implementation of RNTCP. Creating awareness through specific, effective and innovative IEC and BCC campaigns in tribal areas is required for the successful implementation of DOTS.